KETIDAKPASTIAN LINGKUNGAN, DESENTRALISASI, TERHADAP HUBUNGAN KARAKTERISTIK INFORMASI SISTEM AKUNTANSI MANAJEMEN DAN KINERJA MANAJERIAL (Studi Empiris Perusahaan Manufaktur Di Kabupaten Semarang) - Dona Fitrianingrum; Provita Wijayanti (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2011)
Management accounting information plays in helping to predict the possible consequences of various alternative actions can be performed on a variety of activities such as planning, controlling and decision making. The existence of management accounting information will also enhance the ability of managers to understand the state of the environment and work well inidentifying the relevant activity. The purpose of this study was to examine the Environmental Uncertainty and Decentralization Of Relationship Characteristics of Accounting Information and Managerial Performance. This study is an empirical study with convenience sampling technique in data collection. The population in this study is the operations manager, production, marketing and manufacturing company in Semarang regency. Based on sampling data obtained by 80 respondents. The analytical method used was Moderating Regression Analysis. The results of this study is the broad scope of interaction with the environment uncertainty, aggregation andinteraction with the environment uncertainty is shown to be positively related to managerial performance, and timeliness of interaction with the environment uncertainty, interaction uncertainty integration with the environment proved to be positively related to managerial performance. While the interaction with the broad scope of decentralization, the interaction with the timeliness of decentralization, integration with decentralized interaction proved a positive influence on managerial performance, and interaction with the aggregation of decentralization has not been proven positive effect on managerial performance.Keywords: Broad Scope, Timeliness, Aggregation, integration, environmental uncertainty, decentralization, and Managerial Performance.